30th Anniversary of comprehensive two‐dimensional gas chromatography: Latest advances. Issue 3 (21st January 2021) - Zanella, Delphine; Focant, Jean‐François; Franchina, Flavio A.
Abstract: In this review, we report on the latest (2020‐Early 2021) instrumental advances and applications of comprehensive two‐dimensional gas chromatography (GC×GC), including its hyphenation with novel upstream or downstream processes (sample preparation approaches or detection technologies). We also discuss software and analysis workflow developments necessary to elaborate the dense chemical information obtained. Thirty years after its inception, the use of GC×GC, as the main analytical tool or as a complementary platform, is undoubtedly shifting toward more applied challenges in a vast breadth of applications. Therefore, we consider the major fields (energy, fuel, foodstuff, plant, biological, and environmental) in which GC×GC has been successfully used, discussing some of the recent innovative research works.